O pedômetro como instrumento para avaliação do sedentarismo em adolescentes de escolas públicas da região leste de Goiânia - VITORINO, Priscila Valverde de Oliveira (2011)
Introduction: Sedentarism is an important risk factor for several diseases. The lifestyle of the population, especially teenagers has led to increased sedentary lifestyle and overweight. Adolescence is the period most conducive to acquire healthy habits that can last into adulthood. Knowledge of the prevalence of sedentary lifestyle and associations with other factors may help in the seek of public health strategies to combat and prevent diseases. Aim: Evaluating the pedometer as an instrument to measure physical activity of teenagers between 14-18 years in public schools, compared with that held by the International of Physical Activity Questionnaire (IPAQ); comparing the prevalence of sedentarism according to an assessment by the IPAQ and pedometer; evaluating the agreement and correlation between measurements obtained by the instruments, identifying the prevalence of physical inactivity by gender, age, body mass index (BMI) and waist circumference (WC). Methods: Cross-sectional, descriptive study that evaluated 132 teenagers between 14 -18 years from four public schools in the Eastern Region of Goiânia. Data were collected regarding gender, age, BMI, WC and evaluating of inactivating through the IPAQ and Pedometer. Results: The prevalence of sedentarism was 56.8%; 43.9%; 19.7% and 8.3% (p= 0,021) for the pedometer 10.000 steps/day, IPAQ without walking, IPAQ with walking and pedometer 4.012 steps/day, respectively. There is no correlation between the results measured by the IPQA instruments and pedometer the concordance (Kappa index) between methods was weak (k=0,021). The prevalence of sedentary girls 68.6% (n= 48) was higher than the prevalence of sedentary boys 43.5% (n= 27) only when the evaluation was performed by the pedometer with a cutoff of 10,000 steps/day (p= 0.004). Conclusion: The prevalence of sedentarism is higher with IQPA. The agreement between the measurement instruments is weak and the correlation is nonexistent. Girls are more sedentary than boys when the instrument for evaluation of a sedentary lifestyle is the pedometer with a cutoff of 10,000 steps/day.